Difference and Disability in the Medieval Islamic World Blighted Bodies - Richardson, Kristina (Edinburgh University Press, 2012)
Medieval Arab notions of physical difference can feel singularly arresting for modern audiences. Did you know that blue eyes, baldness, bad breath and boils were all considered bodily 'blights', as were cross eyes, lameness and deafness? What assumptions about bodies influenced this particular vision of physical difference? How did blighted people view their own bodies? Through close analyses of miniature paintings, personal letters, (auto)biographies, travel narratives, erotic poetry, religious polemics, diaristic chronicles and theological tracts, you will learn about cultural views and lived experiences of disability and difference.